Hubungan Lingkungan Fisik dan Tindakan PSN dengan Penyakit Demam Berdarah Dengue di Wilayah Buffer Kantor Kesehatan Pelabuhan Kelas II - Adi Andi Anwar (Jurnal Ilmiah Manuntung, 2015)
Dengue Hemorrhagic Fever (DHF) is a health problem in Indonesia, which can lead to the extraordinary events (plague).The development of science and technology affect the development of social and cultural, agricultural, industrial, mining and public mobility. The second-class Port Health Office Samarinda is included as endemic area; with the 33 total numbers of cases in 2013 and there were 20 cases started from January to August 2014. The purpose of this study was to find out the relationship between water shelter, humidity and eradication of mosquito breeding toward DHF in buffer area of the Second-Class Port Health Office Samarinda. This type of research is an analytical survey method with cross sectional approach. It is included as the research which learns the dynamics of the correlation between risk factors and effects, using observation or data collection approach at once.  The sample of this study was 140 respondents with observation and measurement using Mann Whitney and Chi Square tests. Variables of this study consisted of dependent variable, which is DHF and independent variables are the water shelter, humidity and eradication of mosquito breeding. The findings showed there was relationship between water shelters (ρ value0,031), and humidity (ρ value0,046), and also eradication of mosquito breeding (ρ value0,000). Based on the results of this study, it is expected to the healthcare institutions to give frequent health education to the society about the dangers of DHF, control the breeding of mosquitoes, and prevent mosquitoes’ bites in order to prevent infected by this disease.